Co-Precipitation Synthesis of Lanthanum Borates with Different Morphologies - Argun, Sevgi; Dumanli, F. Tugce Senberber; Kipcak, Azmi Seyhun; Tugrul, Nurcan; Derun, Emek Moroydor (PLEIADES PUBLISHING LTD, 2023)
In this study, different formulations of lanthanum borates were successfully prepared by using two-step co-precipitation method. In the first step of hydrothermal synthesis, lanthanum source was selected as La(NO3)(3).6H(2)O and boron source was selected as Na2B4O7 center dot 10H(2)O. Capping agents were selected as C18H34O2 (OA), C19H42BrN (CTAB), C6H15N (TEA) and C4H7NO (PVP). The synthesis conditions were set to 180 degrees C reaction temperature and 4 h reaction time, capping agents were added as 1 ml. After the synthesis products were purified and dried. At the second-step dried powders were pelleted and calcined for 2 h at 1000 degrees C in air atmosphere. Characterization studies of X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR) and Scanning electron microscope (SEM) were applied to final products. According to the XRD results, three different phases were obtained as La(BO2)(3), LaBO3 and LaB3O6, with powder diffraction file number (PDF no.) of 00-023-1140, 00-012-0762 and 01-073-1150. Obtained FTIR spectrum band values were consistent with the boron compounds and SEM analysis showed that the particle sizes of 260-300 nm obtained at non-capped product and particle sizes decreased in the capped products.
Keywords: Borates; capping agent; co-precipitation synthesis; morphology; SOLID-STATE METHOD; PRECURSOR; Materials Science